Development of e-module based on Premna serratifolia research to identify functional group of secondary metabolites - Arni, Arni; Hadiarti, Dini; Kurniati, Tuti (Pascasarjana Universitas Negeri Medan, 2024)
The absence of self-learning resources tailored to the characteristics of students to study the identification of secondary metabolite functional groups based on research on medicinal plants in West Kalimantan necessitates the development of an e-module. This research aimed to develop an e-module based on Premna serratifolia research to identify functional groups in the Natural Products Chemistry course, ensuring its validity and practicality. The ADDIE model was followed, which included analysis, design, development, implementation, and evaluation stages, to develop this e-module. Data were collected using an indirect communication technique by distributing questionnaires. The research sample comprised 30 participants from Universitas Muhammadiyah Pontianak, Universitas Tanjungpura University, and Akademi Farmasi Yarsi Pontianak. The e-module was validated by nine validators, including subject matter experts, media experts, and language experts, with a validity score of 89.3%, indicating it is highly valid. The module was also found to be highly practical through individual, small-group, and large-group testing, with scores of 95.6%, 94.3%, and 98.3%, respectively. This research-based e-module is considered highly suitable and practical as a learning resource for identifying functional groups.